LOS PRINCIPIOS CONSTITUCIONALES DE ESTABILIDAD Y CONTINUIDAD LABORAL DEL SERVIDOR PÚBLICO QUE LABORA POR CONTRATO DE SERVICIOS OCASIONALES - SARANGO BENAVIDES, COSME DANILO (2015)
The thematic related to my grade thesis takes for title: "The constitutional principles of stability and labor continuity of the public servant that he/she works for contract of occasional services", this topic makes reference to the labor stability that you/they have the public servants that through recruiting for occasional services in continuous form come working in the public institutions, as the Court of Justica, Universities, Government, among others. The public servants when being hired again demonstrate their development in the institution and their efficiency in the work, for what you/they are allowed to continue working, however, at least they wait they are no longer hired, spite to have lent their services for more than two serial years. In these cases it should be summoned them mainly to a competition of merits and opposition to these servants that have been unwrapped in the public administration with wide experience. When analyzing the Constitution of the Republic of the Ecuador in the Art. 229, we find that the rights of the servants and public servants are irrenunciables. The law will define the organism rector as regards human resources and remunerations for the whole public sector and it will regulate the entrance, ascent, promotion, incentives, disciplinary régime, stability, remuneration system and ceasing of functions of its servants. This constitutional disposition is being inobservada in spite of being inmersos in a Constitutional State of Rights and Constitutional Supremacy, rezagos of vulneración of people's rights still 6 exists in laws of smaller hierarchy that injure the right to the stability and labor continuity that desempañando comes some public servants with the benefit of contracts of occasional services, as the Art determines it 58 of the Organic Law of the Public Servant that he makes reference to the contracts of occasional services, indicating the recruiting of personal occasional he won't be able to surpass twenty percent of the entirety of the personnel of the contracting entity; in case you will overcome this percentage he/she will have the previous authorization of the Ministry of Labor Relationships, these contracts won't be able to exceed of twelve months of duration or until it culminates the remaining time of the fiscal exercise in course. This type of contracts, for its nature, in no way will represent labor stability in the same one, neither acquired right for the emission of a permanent appointment, being been able to give had finished in any moment, that which will be able to consist of the text of the respective contracts. This norm contravenes expressed constitutional disposition, as well as of its same law that in the Art. 23 determine; they are right irrenunciables of the servants and public servants: to). to Enjoy Stability in their position; that is to say, the own Organic Law of the Public Service contains juridical incongruities that should be repealed. The theoretical, juridical and doctrinal storing, the study of concrete cases, the application of surveys and interviews, he/she allowed to obtain approaches with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of the objectives and the contrastación from the relating outlined hypothesis to this practice; so much the Constitution of the 7 Republic of the Ecuador, as the other laws of the public servant that tipifican their rights to the stability and continuity.